Prethymic Cytoplasmic CD3 Negative Acute Lymphoblastic Leukemia or Acute Undifferentiated Leukemia: A Case Report - Cannizzo, Elisa; Carulli, Giovanni; Del Vecchio, Luigi; Azzarà, Antonio; Galimberti, Sara; Ottaviano, Virginia; Preffer, Frederic; Petrini, Mario (Case Reports in Hematology, 2011)
Acute undiffentiated leukemia (AUL) is an acute leukemia with no more than one membrane marker of any given lineage. Blasts often express HLA-DR, CD34, and/or CD38 and may be positive for terminal deoxynucleotidyl transferase (TdT). The expression of CD34, HLA-DR, and CD38 has been shown in pro-T-ALL, although in this case, blasts should also express CD7 and cyCD3. However, some cases of T-ALL without CD3 in the cytoplasm and all TCR chain genes in germ line configuration are reported, features that fit well with a very early hematopoietic cell. We report a case of acute leukemia CD34+/−HLADR+CD7+CD38+cyCD3− in which a diagnosis of AUL was considered. However the blasts were also positive for CD99 and TCR delta gene rearrangement which was found on molecular studies. Therefore a differential diagnosis between AUL and an early cyCD3 negative T-ALL was debated.